2008
DOI: 10.1901/jeab.2008.89-183
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Imitation of Hand‐to‐body Gestures in 2‐ and 3‐year‐old Children

Abstract: Twenty children, ten 2-year-olds and ten 3-year-olds, participated in an AB procedure. In the baseline phase, each child was trained the same four matching relations to criterion under intermittent reinforcement. During the subsequent imitation test, the experimenter modeled a total of 20 target gestures (six trials each) interspersed with intermittently reinforced baseline trials. In each session, target gestures were selected in a pre-randomized sequence from: Set 1-ear touches; Set 2-shoulder touches; Set 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 39 publications
5
19
0
Order By: Relevance
“…In the matching tests that followed baseline matching training and prior to the first round of tact training (i.e., across Test 1 sessions for the first pair of targets, and Test 1 and Test 2 for the second pair of targets), out of a total of 12 untrained target gestures across all 3 children, 6 were infrequently matched, and the remaining 6 were not matched at all. Our data show no evidence that repeated modeling of target gestures resulted in increased matching, which is consistent with our previous findings (Erjavec & Horne, 2008; Erjavec et al, 2009; Horne & Erjavec, 2007).…”
Section: Resultssupporting
confidence: 93%
“…In the matching tests that followed baseline matching training and prior to the first round of tact training (i.e., across Test 1 sessions for the first pair of targets, and Test 1 and Test 2 for the second pair of targets), out of a total of 12 untrained target gestures across all 3 children, 6 were infrequently matched, and the remaining 6 were not matched at all. Our data show no evidence that repeated modeling of target gestures resulted in increased matching, which is consistent with our previous findings (Erjavec & Horne, 2008; Erjavec et al, 2009; Horne & Erjavec, 2007).…”
Section: Resultssupporting
confidence: 93%
“…It seems likely that body parts that commonly feature in social routines would be learned ahead of those that are not commonly touched or named. For example, Erjavec and Horne (2008) have reported that shaping of children's responses in social games and other interactions with caregivers correlates with the accuracy of children's body touch responses on an imitation task. In this study, 2‐ to 3‐year‐old children performed significantly more matching responses to target models that commonly featured in nursery matching games, than to target gestures that had no such learning history, even though the two sets of target hand‐to‐body touches were similar in terms of complexity and production difficulty.…”
Section: Introductionmentioning
confidence: 99%
“…When prompted simply to "do as I do," when no target was apparent (i.e., movements simply hovered over an area of the table), children tended to respond in the mirror style (but see Mizuguchi, Sugimura, Suzuki, & Deguchi, 2011). Similarly, Erjavec and Horne (2008) more recently reported a mirror-style bias in 2-and 3-year-olds when responding to modelled hand and arm movements.…”
mentioning
confidence: 99%